Efeito bioherbicida de extratos de sorgo no controle de Amaranthus virids L. - Santos, Wanderson Silva dos (2024)
The present study aimed to identify the bioherbicidal effect of sorghum leaf extract on the control of Amaranthus viridis (L.), as well as discover the appropriate phenological stage of sorghum to obtain the extract with high bioherbicidal action. The work was conducted in a greenhouse at the State University of Goiás, Câmpus Sul, Ipameri Unit, Ipameri, Goiás. The experiment was conducted in a completely randomized design in a 3 x 4 factorial scheme, using sorghum leaf extract extracted in three phenological stages (E1, E3 and E6) and four percentage doses of the extract (0%, 25%, 50% and 100% of the diluted extract), with three replications. Three applications of the extract were carried out on the plants and the soil, with the aid of a manual sprayer, at three times: at 33, 39 and 43 days after emergence (DAE), during the pigweed & 39;s development. At 50° DAE, the following evaluations were carried out: number of leaves, leaf area, plant height, plant biomass, stem, leaf, root mass ratios, SPAD and root length. According to the data, it was found that the doses of sorghum leaf extract influenced the number of leaves, leaf area, plant height, plant biomass and leaf mass ratio. The results indicate that sorghum leaf extract can be obtained at different phenological stages of the sorghum plant, without loss of bioherbicidal action for pigweed. The results of the regression analysis demonstrate that plant biomass, number of leaves, leaf area and stem mass ratio of A. viridis reduced linearly as the doses of sorghum extract increased. For each increased unit of sorghum extract (%) there was a reduction of up to 0,02 g for plant biomass, 0,25 unit for number of leaves, 1,56 cm² for leaf area and 0.08% for leaf ratio. stem mass. The sorghum leaf extract obtained from the three phenological stages (E1, E3 and E6) of sorghum plants, has bioherbicidal action and slows down the growth of pigweed plants (Amaranthus viridis L.), especially when used at a concentration of 100 % of extract.